Electrically conductive and elastoplastic carbon nanohybrid preform reinforced by physical cross-linking. Issue 4 (2nd October 2019) - Wang, Baichen; Zhu, Yanfei; Li, Junjie; Li, Wei; Gao, Yu
ABSTRACT: Efficient buildup of carbon nanomaterial network with isotropic structure and performances in viscous polymer bulk has been of intense interest for abundant range of applications. Herein, a conductive and elastoplastic carbon nanohybrid preform is prepared. The strategy for assembling structurally intact carbon nanotubes (CNTs) and amphiphilic graphene oxide (GO) into integral carbon nanohybrid framework is implemented by using 2-ethyl-4-methylimidazole (EMI) during an undisturbed reaction. The as-synthesized porous carbon nanohybrid preform with sandwich cell wall was characterized with respect to wettability, electrical conductivity, and structural robustness to evaluate the structural and functional synergies from GO sheets and CNTs. Significantly increased conductivity is ascribed to the networking sp 2 -hybridized carbon domains interconnected by CNT bridges. The hydrogen-bonded EMI chains functioning as physical cross-linking are responsible for the elastoplasticity of carbon nanohybrid preform. A mechanism underlying is proposed for the conversion from common carbon nanomaterials to three-dimension multifunctional reinforcement.